Different disulfide bridge connectivity drives alternative folds in highly homologous Brassicaceae trypsin inhibitors. Issue 12 (6th November 2015) - Leboffe, Loris; Angelini, Riccardo; Menegatti, Enea; Polticelli, Fabio; Ascenzi, Paolo
Abstract: Low‐molecular‐mass trypsin inhibitors from Arabidopsis thaliana, Brassica napus var. oleifera, and Sinapis alba L. (ATTI, RTI, and MTI, respectively) display more than 69% amino acid sequence identity. Among others, the amino acid sequence Cys‐Ala‐Pro‐Arg‐Ile building up the inhibitor reactive site, and the eight Cys residues forming four disulfide bridges are conserved. However, the disulfide bridge connectivity of RTI and MTI (C1 ‐C3, C2 ‐C4, C5 ‐C6, and C7 ‐C8 ) is different from that of ATTI Cys (C1 ‐C8, C2 ‐C5, C3 ‐C6, and C4 ‐C7 ). Despite the different disulfide bridge connectivity, the reactive site loop of ATTI, RTI, and MTI is solvent exposed permitting trypsin recognition. Structural considerations here reported suggest that proteins showing high amino acid sequence identity and common functional properties could display different three‐dimensional structures. This may reflect high inhibitor plasticity in relation to plant–pathogen interactions, plant tissue development as well as the different redox potential of cell compartments. © 2015 IUBMB Life, 67(12):966–970, 2015